Comparison of the Long-Term Outcomes of Endoscopic Papillary Large Balloon Dilation Alone versus Endoscopic Sphincterotomy for Removal of Bile Duct Stones - Tao Li; Jun Wen; Like Bie; Biao Gong (Gastroenterology Research and Practice)
Background and Aims. Endoscopic papillary large balloon dilation (EPLBD) alone is an alternative to endoscopic sphincterotomy (EST) for treatment of common bile duct (CBD) stones. However, limited data exists regarding comparison of the long-term outcomes for these techniques. In this study, we compared the long-term outcomes after EST with those after EPLBD alone for removal of CBD stones. Methods. The records of patients with EST or EPLBD alone referred for CBD stones retrieval between June 2008 and July 2015 were retrospectively reviewed. Complete stone clearance, ERCP-related adverse events, and late biliary complications during long-term follow-up were analyzed. Results. Basic patient characteristics were similar between the groups that underwent EST (n=60) and EPLBD alone (n=161). EPLBD compared with EST resulted in similar outcomes in terms of complete stone clearance (99.4% versus 100%, P=0.54) and ERCP-related adverse events (6.8% versus 6.7%, P=1.00). The mean duration of the follow-up was 74.5 months and 71.6 months who underwent EST and EPLBD alone, respectively (P=0.42). Late biliary complications were occurred frequently in the EST group than in the EPLBD alone group (11 [18.6%] versus 16 [10.2%]), although the difference did not reach statistical significance (P=0.11). Multivariate analysis showed that mechanical lithotripsy ([OR], 2.815; 95% CI, 1.148–6.902; P=0.024) was significantly associated with late biliary complications. Conclusion. As an alternative to EST, EPLBD has similar efficacy and safety for managing CBD stones. During long-term follow-up, patients who underwent EPLBD alone may have fewer late biliary complications compared with those after EST. In addition, mechanical lithotripsy may be an independent risk factor for late biliary complications.